2022
DOI: 10.1002/aisy.202200166
|View full text |Cite
|
Sign up to set email alerts
|

Ingestible Functional Magnetic Robot with Localized Flexibility (MR‐LF)

Abstract: The gastrointestinal (GI) tract plays a crucial role in the human body as a naturally evolved interface between the body and its environment. Ingestible electronics perform surgical-free screenings and diagnoses within the GI tract and have been proposed since 1957. [1][2][3][4] Recent advancements have demonstrated the ability to integrate ingestible electronics with sensing, actuation, and drug delivery capabilities, with several examples that have been FDA approved and are in clinical use. [5][6][7][8] For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…However, how to remotely control the collection and dispersion of each functional module is the focus of research. A design of centralized compartment in magnetic robot by imparting localized flexibility was demonstrated, that enables capsule robot to be readily integrated with functional modular, such as commercial electronics and medication [76]. Furthermore, adaptive magnetic levitation is an ideal way for capsule robots to move.…”
Section: Medical Operation Of Capsule Robotsmentioning
confidence: 99%
“…However, how to remotely control the collection and dispersion of each functional module is the focus of research. A design of centralized compartment in magnetic robot by imparting localized flexibility was demonstrated, that enables capsule robot to be readily integrated with functional modular, such as commercial electronics and medication [76]. Furthermore, adaptive magnetic levitation is an ideal way for capsule robots to move.…”
Section: Medical Operation Of Capsule Robotsmentioning
confidence: 99%
“…In recent years, microrobots have shown great advantages in the field of biomedical applications. With the development of microrobots, various aspects such as their driving methods [ 2 , 3 , 4 , 5 , 6 ], recognition and tracking [ 7 , 8 ], biosafety [ 9 ], targeted drug delivery methods [ 10 , 11 , 12 ], and multi-functional integration [ 13 , 14 ] have attracted widespread attention. For example, a magnetically driven rotary ablation catheter robot [ 15 ] was employed to remove calcified deposits from arterial stenosis and occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] Among various methods, applying an external magnetic field to create a torque or force on the soft actuator is one of the simplest yet effective actuation approaches. [34][35][36][37][38][39][40][41][42][43][44] More importantly, this actuation method is transparent and noninvasive, and high temporal resolution is possible by controlling the amplitude, gradient, and direction of the magnetic field. Although some interesting studies on sample capturing and trapping have been reported using soft actuator platforms, [45][46][47] their use in hot-spot engineering is still very limited.…”
Section: Introductionmentioning
confidence: 99%